2023
DOI: 10.1200/jco.22.00392
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib Combined With Transarterial Chemoembolization as First-Line Treatment for Advanced Hepatocellular Carcinoma: A Phase III, Randomized Clinical Trial (LAUNCH)

Abstract: PURPOSE Lenvatinib (LEN) is a first-line therapy for patients with advanced hepatocellular carcinoma (HCC); however, it has shown modest survival benefits. Therefore, we aimed to compare clinical outcomes of LEN combined with transarterial chemoembolization (LEN-TACE) versus LEN monotherapy in patients with advanced HCC. MATERIALS AND METHODS This was a multicenter, randomized, open-label, parallel group, phase III trial. Patients with primary treatment-naive or initial recurrent advanced HCC after surgery wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
237
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(242 citation statements)
references
References 25 publications
5
237
0
Order By: Relevance
“…Moreover, we found that combination locoregional therapy was an independent factor for both better PFS and OS. This result was consistent with the results of previous studies that found that adding locoregional therapy to a lenvatinib plus a PD-1 inhibitor or lenvatinib monotherapy therapeutic regimen could lead to a high response and long survival [9,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we found that combination locoregional therapy was an independent factor for both better PFS and OS. This result was consistent with the results of previous studies that found that adding locoregional therapy to a lenvatinib plus a PD-1 inhibitor or lenvatinib monotherapy therapeutic regimen could lead to a high response and long survival [9,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Most cases are unresectable HCC (uHCC) [1,2]. Patients with uHCC exhibit a median overall survival (OS) of only 11.8-21.2 months for systematic therapy in phase III studies [3][4][5][6][7][8][9][10] and real-world studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows reported outcomes of RCTs for TACE in the treatment of HCC. [13][14][15][16][28][29][30][31][32][33][34][35][36][37][38][39][40]…”
Section: Response Assessment and Treatment Outcomesmentioning
confidence: 99%
“…However, making a binary therapeutic choice in a cancer as complex as HCC is often neither feasible nor efficacious. Combinatorial treatments, such as levatinib plus transarterial chemoembolization, have been shown in the recently published LAUNCH trial (http://clinicaltrials.gov identifier NCT03905967) to provide a significant survival benefit, further expanding the options available to patients and clinicians 7 . In addition, HCC outcomes are defined by the competing mortality risk conferred by advanced cirrhosis, a group that is excluded in clinical trials.…”
Section: Figurementioning
confidence: 99%
“…Combinatorial treatments, such as levatinib plus transarterial chemoembolization, have been shown in the recently published LAUNCH trial (Clini calTr ials.gov identifier NCT03905967) to provide a significant survival benefit, further expanding the options available to patients and clinicians. 7 In addition, HCC outcomes are defined by the competing mortality risk conferred by advanced cirrhosis, a group that is excluded in clinical trials. In practice, it is necessary to tailor therapy for advanced HCC based not just on cost effectiveness but also on patient characteristics, payor mix, societal expectations, and institutional expertise.…”
Section: Conflicts Of Interestmentioning
confidence: 99%